Golf ball
The golf ball design addresses the challenge of controlling iron shots by using a spherical core with a specific hardness distribution and a layered structure, resulting in improved feel, reduced rolling distance variability, and enhanced controllability.
Patent Information
- Application Number
- JP2023172934
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-04
- Publication Date
- 2025-04-16
AI Technical Summary
Existing golf balls with high backspin for improved controllability in iron shots suffer from increased rolling distance variability due to unstable impact points, making it difficult for average golfers to control the ball's distance accurately. Additionally, these balls often have a hard feel, which is undesirable for iron shots.
A golf ball design featuring a spherical core made from a rubber composition containing natural rubber, methacrylic acid, and a crosslinking initiator, with a specific hardness distribution that ensures a soft feel and controlled spin performance. The core is covered by an intermediate layer and an outermost layer, optimizing the ball's aerodynamics and spin characteristics.
The golf ball achieves a good hitting feel with irons, reduces rolling distance variability, and enhances controllability while minimizing wind influence, thanks to its optimized spin performance and soft feel.
Smart Images

Figure 2025063591000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a golf ball, and more particularly to a golf ball having a spherical core, an intermediate layer, and an outermost cover layer. [Background technology]
[0002] Iron shots are shots to carry the ball to the green or a desired location, and the important thing is not the distance it travels, but the control it has to be able to hit the ball the desired distance. The distance a golf ball travels is the sum of the distance it travels from when it is hit until it lands on the ground (the carry) and the distance it travels from when it lands until it stops (the run). Therefore, in order to control the distance a golf ball travels, it is necessary to control both the run and the carry.
[0003] Here, the face of the golf club has a loft angle. When a golf ball is hit with this golf club, the golf ball is launched with a launch angle according to the loft angle. The golf ball also generates backspin due to the loft angle. The golf ball flies with backspin. The higher the backspin speed, the smaller the run. In other words, by using a golf ball with a high backspin speed, the player can easily stop the golf ball at the target point. Therefore, a golf ball with excellent spin performance has high controllability.
[0004] In addition, spherical cores made from various rubber materials have been proposed as the spherical cores of golf balls. For example, Patent Document 1 describes a driving range golf ball obtained by vulcanizing a composition containing 3 to 35 parts by weight of low-resilience rubber, 20 to 30 parts by weight of methacrylic acid, and 20 to 50 parts by weight of a metal compound capable of forming a metal salt with methacrylic acid, per 100 parts by weight of base rubber (see Patent Document 1 (Claim 1, page 3, upper left column, lines 11 to 17)).
[0005] Patent Document 2 describes a golf ball for use at driving ranges obtained from a composition containing 100 parts by weight of a base rubber, 3 to 35 parts by weight of 10 to 60 mol % epoxidized natural rubber, 20 to 35 parts by weight of methacrylic acid, and 20 to 50 parts by weight of zinc oxide (see Patent Document 2 (Claim 1, page 2, lower left column, line 4 to lower right column, line 2)). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 60-92780 [Patent Document 2] Japanese Patent Application Publication No. 61-71069 Summary of the Invention [Problem to be solved by the invention]
[0007] The run (rolling distance) of an iron shot can be controlled by improving the spin performance of the golf ball and increasing the amount of backspin. However, as the amount of backspin increases, the ball will fly up and the highest point of the ball will become higher, making the golf ball more susceptible to the effects of wind. However, it is difficult for average golfers to read the wind, making it difficult to control the flight distance of an iron shot. Furthermore, the amount of spin varies depending on the variation in the impact point, but since the average golfer does not have a stable impact point, it is difficult to control the amount of spin. And with a golf ball with an increased amount of spin, the amount of change in the amount of spin due to the variation in the impact point becomes large, so the amount of change in the distance the ball stops (the amount of roll) also becomes large, making it difficult to adjust the flight distance. In addition, in order to get the right feeling for the distance when making an iron shot, the feel of the shot is also important, so it is preferable that the feel of the shot be soft when making an iron shot. The present invention has been made in view of the above circumstances, and an object thereof is to provide a golf ball having a good hitting feeling at the time of iron shot, a small rolling distance, excellent controllability, a low maximum height, and a small influence of wind.
Means for Solving the Problems
[0008] The golf ball of the present invention that has solved the above problems has a spherical core, an intermediate layer covering the spherical core, and an outermost layer cover covering the intermediate layer. The spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator. The base rubber contains natural rubber, the co-crosslinking agent contains methacrylic acid and / or its metal salt, and the center hardness (H0) of the spherical core, the hardness (H 2.5 ) at a point 2.5 mm in the radial direction from the center of the spherical core, the hardness (H 5.0 ) at a point 5.0 mm in the radial direction from the center of the spherical core, the hardness (H 7.5 ) at a point 7.5 mm in the radial direction from the center of the spherical core, the hardness (H 10 ) at a point 10 mm in the radial direction from the center of the spherical core, the hardness (H 12.5 ) at a point 12.5 mm in the radial direction from the center of the spherical core, the hardness (H 15 ) at a point 15 mm in the radial direction from the center of the spherical core, and the surface hardness (Hs) satisfy the relationship of H0 < H 2.5 < H 5.0 < H 7.5 < H 10 < H 12.5 < H 15 < Hs.
[0009] Since the golf ball of the present invention contains natural rubber as the base rubber of the rubber composition forming the spherical core and contains methacrylic acid and / or its metal salt as the co-crosslinking agent, the initial ball speed at the time of iron shot can be kept low, and the maximum height becomes low. Further, by controlling the hardness distribution of the spherical core, the deformation of the spherical core occurs smoothly, and the hitting feeling of the iron shot becomes good. The golf ball of the present invention provides a good shot feeling upon iron shots, has a short rolling distance for excellent controllability, and has a low peak height for less influence by wind. Effect of the Invention
[0010] According to the present invention, a golf ball can be obtained which provides a good shot feeling when hit with an iron, has a short rolling distance and excellent controllability, and has a low peak height and is less affected by wind. [Brief description of the drawings]
[0011] [Figure 1] 1 is a partially cutaway cross-sectional view showing a golf ball according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The golf ball of the present invention has a spherical core, an intermediate layer enclosing the spherical core, and an outermost cover enclosing the intermediate layer.
[0013] (Spherical core) The spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator.
[0014] The base rubber contains natural rubber (NR), which makes it possible to keep the initial velocity of the ball low when shot with an iron. The natural rubber is produced by harvesting the latex (milky liquid) from a plant that produces natural rubber, by scratching the plant, and coagulating the rubber component contained in the latex. The natural rubber may be used alone or in combination of two or more types.
[0015] Examples of plants that produce natural rubber latex include Hevea brasiliensis and Hevea serowata of the Euphorbiaceae family, Rubber tree, Panagium, and Lagos of the Mulberry family, Gum arabicum, Tragacanth, Curculionidae, Zanzibar vine, Huntsumia elastica, and Urceola of the Fabaceae family, Guayule, and Rubber dandelion of the Asteraceae family, Gutta-percha, Balata, and Sapodilla of the Sapotaceae family, Morning glory of the Asclepiadaceae family, and Eucommia of the Eucommaceae family.
[0016] The natural rubber may be a CV grade in which the rubber viscosity is stabilized by adding a viscosity stabilizer or the like to the raw latex, or a non-CV grade in which the rubber viscosity is not stabilized. These may be used alone or in combination of two or more. Among these, a CV grade having a particularly stable viscosity is preferred. The natural rubber may be either SMR (standard Malaysian rubber) or SVR (standard Vietnam rubber).
[0017] The natural rubber is cis-1,4-polyisoprene, and either sheet rubber or block rubber can be used. Natural rubber also includes modified natural rubbers, such as epoxidized natural rubber, methacrylic acid modified natural rubber, halogen modified natural rubber, deproteinized natural rubber, maleic acid modified natural rubber, sulfonic acid modified natural rubber, and styrene modified natural rubber. Of these, it is preferable that the natural rubber does not contain epoxidized natural rubber.
[0018] The natural rubber is preferably Technical Specified Rubbers (TSR) or Ribbed Smoked Sheet (RSS). The natural rubber may contain a viscosity stabilizer.
[0019] The Mooney viscosity (ML 1+4(100°C)) is preferably 30 or more, more preferably 35 or more, and even more preferably 40 or more, and is preferably 80 or less, more preferably 75 or less, and even more preferably 70 or less. In this specification, the Mooney viscosity (ML 1+4 (100°C) is the value measured in accordance with JIS K6300 (2013) using an L rotor with a preheating time of 1 minute, rotor rotation time of 4 minutes, and at 100°C.
[0020] The base rubber may contain only natural rubber, or may contain natural rubber and synthetic rubber. When the base rubber contains natural rubber and synthetic rubber, the content of natural rubber in 100% by mass of the base rubber is preferably 10% by mass or more, more preferably 25% by mass or more, and even more preferably 40% by mass or more, and is preferably less than 100% by mass, more preferably 90% by mass or less, and even more preferably 80% by mass or less. If the content is 10% by mass or more, the hitting feel on driver shots is good, and if it is less than 100% by mass, the ball rolls well when puttering, making it easier to get the distance right.
[0021] Examples of the synthetic rubber include diene rubbers such as polybutadiene rubber (BR), polyisoprene rubber (IR), styrene polybutadiene rubber (SBR), chloroprene rubber (CR), butyl rubber (IIR), and acrylonitrile butadiene rubber (NBR); and non-diene rubbers such as ethylene propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), urethane rubber, silicone rubber, acrylic rubber, epichlorohydrin rubber, polysulfide rubber, fluororubber, and chlorosulfonated polyethylene rubber. These may be used alone or in combination of two or more.
[0022] The base rubber may contain a diene rubber as a synthetic rubber. In this case, the content of the diene rubber in 100% by mass of the base rubber is preferably more than 0% by mass, more preferably at least 10% by mass, even more preferably at least 20% by mass, and is preferably at most 90% by mass, more preferably at most 75% by mass, even more preferably at most 60% by mass.
[0023] The base rubber preferably contains polybutadiene rubber as a diene rubber. In particular, it is more preferable that the base rubber contains high-cis polybutadiene having cis-1,4-bonds in an amount of 40% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more. The content of high-cis polybutadiene in the diene rubber is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. It is also preferable that the diene rubber contains only high-cis polybutadiene rubber.
[0024] The high-cis polybutadiene preferably has a 1,2-vinyl bond content of 2.0% by mass or less, more preferably 1.7% by mass or less, and further preferably 1.5% by mass or less.
[0025] The high-cis polybutadiene is preferably one synthesized using a rare earth element catalyst. In particular, the use of a neodymium-based catalyst using a neodymium compound, which is a lanthanum series rare earth element compound, is preferred because it can produce a polybutadiene rubber having a high content of 1,4-cis bonds and a low content of 1,2-vinyl bonds with excellent polymerization activity.
[0026] The high cis polybutadiene preferably has a molecular weight distribution Mw / Mn (Mw: weight average molecular weight, Mn: number average molecular weight) of 2.0 or more, more preferably 2.2 or more, even more preferably 2.4 or more, and preferably 6.0 or less, more preferably 5.0 or less, even more preferably 4.0 or less. If the molecular weight distribution (Mw / Mn) of the high cis polybutadiene is within the above range, the workability is improved. The molecular weight distribution is measured by gel permeation chromatography (manufactured by Tosoh Corporation, "HLC-8120GPC") using a differential refractometer as a detector under the conditions of column: GMHHXL (manufactured by Tosoh Corporation), column temperature: 40°C, and mobile phase: tetrahydrofuran, and is calculated as a standard polystyrene equivalent value.
[0027] The Mooney viscosity (ML 1+4 (100° C.) is preferably 30 or more, more preferably 32 or more, and even more preferably 35 or more, and is preferably 140 or less, more preferably 120 or less, and even more preferably 100 or less.
[0028] The co-crosslinking agent has the effect of crosslinking rubber molecules by graft polymerization with the molecular chains of the base rubber. The co-crosslinking agent contains methacrylic acid and / or a metal salt thereof. By including methacrylic acid and / or a metal salt thereof as the co-crosslinking agent, the spin performance upon iron shots is improved.
[0029] Examples of metal ions constituting the metal salt of methacrylic acid include monovalent metal ions such as sodium, potassium, and lithium, divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium, trivalent metal ions such as aluminum, and other ions such as tin and zirconium. The above metal components can be used alone or as a mixture of two or more kinds.
[0030] The rubber composition preferably uses methacrylic acid as a co-crosslinking agent.
[0031] The co-crosslinking agent may contain, in addition to methacrylic acid and / or its metal salt, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) and / or its metal salt. Examples of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) include acrylic acid, fumaric acid, maleic acid, and crotonic acid.
[0032] Examples of metals constituting the metal salt of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) include monovalent metal ions such as sodium, potassium, and lithium; divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium; trivalent metal ions such as aluminum; and other ions such as tin and zirconium. The metal components can be used alone or as a mixture of two or more kinds. Among these, divalent metals such as magnesium, calcium, zinc, barium, and cadmium are preferred as the metal components. By using a divalent metal salt of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, metal crosslinks are easily formed between rubber molecules.
[0033] When the co-crosslinking agent contains, in addition to methacrylic acid and / or its metal salt, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) and / or its metal salt, the content of methacrylic acid and / or its metal salt in the co-crosslinking agent component is preferably 15% by mass or more, more preferably 17% by mass or more, even more preferably 19% by mass or more, and particularly preferably 50% by mass or more. If the content of methacrylic acid and / or its metal salt is within the above range, the reactivity in the rubber becomes uniform and the quality is stable. It is also preferable to contain only methacrylic acid and / or its metal salt as the co-crosslinking agent, and it is more preferable to contain only methacrylic acid.
[0034] The amount of the co-crosslinking agent, relative to 100 parts by weight of the base rubber, is preferably at least 15 parts by weight, more preferably at least 16 parts by weight, and even more preferably at least 17 parts by weight, and is preferably at most 40 parts by weight, more preferably at most 37 parts by weight, and even more preferably at most 35 parts by weight. If the amount of the co-crosslinking agent is 15 parts by weight or more, the core formed will have an appropriate hardness and the durability of the golf ball will be improved, and if it is 40 parts by weight or less, the core formed will not be too hard.
[0035] The crosslinking initiator is blended to crosslink the base rubber component. As the crosslinking initiator, an organic peroxide is suitable. Specific examples of the organic peroxide include dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and di-t-butyl peroxide. These organic peroxides may be used alone or in combination of two or more. Among these, dicumyl peroxide is preferably used.
[0036] The content of the crosslinking initiator may be appropriately adjusted depending on the desired hardness of the spherical core. The content of the crosslinking initiator is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.7 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, based on 100 parts by mass of the base rubber.
[0037] When the rubber composition contains only methacrylic acid or an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) as a co-crosslinking agent, it is preferable that the rubber composition further contains a metal compound. By neutralizing methacrylic acid or an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) with a metal compound in the rubber composition, substantially the same effect as when a metal salt of methacrylic acid or a metal salt of an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) is used as a co-crosslinking agent, a metal compound may also be used.
[0038] The metal compound is not particularly limited as long as it can neutralize methacrylic acid or an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) in the rubber composition. Examples of the metal compound include metal hydroxides such as magnesium hydroxide, zinc hydroxide, calcium hydroxide, sodium hydroxide, lithium hydroxide, potassium hydroxide, and copper hydroxide; metal oxides such as magnesium oxide, calcium oxide, zinc oxide, and copper oxide; and metal carbonates such as magnesium carbonate, zinc carbonate, calcium carbonate, sodium carbonate, lithium carbonate, and potassium carbonate. The metal compound is preferably a divalent metal compound, and more preferably a zinc compound. The divalent metal compound reacts with methacrylic acid or an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) to form a metal crosslink. These metal compounds may be used alone or in combination of two or more kinds.
[0039] The rubber composition may further contain an organic sulfur compound, but it is also preferable that the rubber composition does not contain an organic sulfur compound. The organic sulfur compound is not particularly limited as long as it is an organic compound having a sulfur atom in the molecule, and examples thereof include organic compounds having a thiol group (-SH) or a polysulfide bond (-SS-, -SSS-, or -SSSS-) having 2 to 4 sulfur atoms, or metal salts thereof (-SM, -SMS-, etc., where M is a metal atom). The organic sulfur compounds can be used alone or in combination of two or more kinds.
[0040] Examples of the organic sulfur compounds include thiophenols, thionaphthols, polysulfides, thiurams, thiocarboxylic acids, dithiocarboxylic acids, sulfenamides, dithiocarbamates, thiazoles, etc. As the organic sulfur compounds, diphenyl disulfides (e.g., diphenyl disulfide, bis(pentabromophenyl) disulfide), thiophenols, and thionaphthols (e.g., 2-thionaphthol) can be suitably used.
[0041] The content of the organic sulfur compound may be appropriately adjusted according to the desired resilience performance of the spherical core. The content of the organic sulfur compound is, for example, preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less, per 100 parts by mass of the base rubber.
[0042] The rubber composition may further contain a carboxylic acid and / or a metal salt thereof. The carboxylic acid and / or a metal salt thereof is preferably a carboxylic acid having 1 to 30 carbon atoms and / or a salt thereof. The carboxylic acid may be either an aliphatic carboxylic acid (saturated fatty acid, unsaturated fatty acid) or an aromatic carboxylic acid (benzoic acid, etc.). When the carboxylic acid and / or a metal salt thereof is blended, the amount of the carboxylic acid and / or a metal salt thereof is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the base rubber.
[0043] The rubber composition may contain additives such as a filler for adjusting the weight, an antioxidant, a peptizer, and a softener, as required.
[0044] The filler used in the rubber composition is mainly used as a weight adjusting agent for adjusting the weight of the final golf ball product, and may be added as needed. Examples of the filler include inorganic fillers such as barium sulfate, calcium carbonate, magnesium oxide, tungsten powder, and molybdenum powder.
[0045] The rubber composition is obtained by kneading the base rubber, the co-crosslinking agent, the crosslinking initiator, and other components that are mixed as necessary. The kneading method is not particularly limited, and may be performed using a known kneading machine such as a kneading roll, a Banbury mixer, or a kneader.
[0046] The spherical core can be molded, for example, by hot pressing the rubber composition for the core. The hot press molding conditions for the rubber composition for the core may be appropriately set depending on the rubber composition, but it is usually preferable to heat the rubber composition at 130°C to 200°C for 10 to 60 minutes, or to heat the rubber composition at 130°C to 150°C for 20 to 40 minutes, and then heat the rubber composition at 160°C to 180°C for 5 to 15 minutes in two stages.
[0047] The spherical core has a central hardness (H0), a hardness at a point 2.5 mm away from the center of the spherical core in the radial direction (H2.5 ) The hardness (H 5.0 ) at a point 5.0 mm radially from the center of the spherical core 7.5 ) The hardness (H 10 ) at a point 7.5 mm radially from the center of the spherical core 12.5 ) The hardness (H 15 ) at a point 10 mm radially from the center of the spherical core 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15 <Hs satisfy the relationship of H0 < H By the hardness distribution of the spherical core satisfying the above requirements, the deformation of the spherical core during impact occurs smoothly, and the hitting feeling during iron shots becomes good.
[0048] The spherical core has the center hardness (H0), hardness (H 2.5 ), hardness (H 5.0 ), hardness (H 7.5 ), hardness (H 10 ), hardness (H 12.5 ), hardness (H 15 ), and surface hardness (Hs) in Shore C hardness, where H 2.5 - H0 < 4, H 5.0 - H 2.5 < 4, H 7.5 - H 5.0 < 4, H 10 - H 7.5 < 4, H 12.5 - H 10 < 4, H 15 - H 12.5 < 4, and it is preferable to satisfy the relationship of Hs - H 15 < 4. Hardness difference (H 2.5 - H0), hardness difference (H 5.0 - H 2.5 ), hardness difference (H 7.5 - H 5.0 ), hardness difference (H 10 - H 7.5 ), hardness difference (H 12.5 - H10 ), hardness difference (H 15 -H 12.5 ) and hardness difference (Hs-H 15 ) within the above range, deformation of the spherical core occurs smoothly upon iron shots, resulting in a better shot feeling.
[0049] The central hardness (H0) of the spherical core and the hardness (H 2.5 ) and hardness difference (H 2.5 -H0) is Shore C hardness, which is preferably 0.3 or more, more preferably 0.4 or more, and even more preferably 0.5 or more, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0050] The hardness (H 2.5 ) and the hardness (H 5.0 ) and hardness difference (H 5.0 -H 2.5 ) is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.7 or more, in Shore C hardness, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0051] The hardness (H 5.0 ) and the hardness (H 7.5 ) and hardness difference (H 7.5 -H 5.0 ) is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.7 or more, in Shore C hardness, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0052] The hardness (H 7.5 ) and the hardness (H 10 ) and hardness difference (H 10-H 7.5 ) is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.7 or more, in Shore C hardness, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0053] The hardness (H 10 ) and the hardness (H 12.5 ) and hardness difference (H 12.5 -H 10 ) is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.7 or more, in Shore C hardness, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0054] The hardness (H 12.5 ) and the hardness (H 15 ) and hardness difference (H 15 -H 12.5 ) is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more, in Shore C hardness, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0055] The hardness (H 15 ) and the surface hardness (Hs) of the spherical core. 15 ) is a Shore C hardness that is preferably greater than 0, more preferably 0.1 or more, and even more preferably 0.2 or more, and is preferably less than 4, more preferably 3.8 or less, and even more preferably 3.5 or less.
[0056] The hardness difference (Hs-H0) between the center hardness (H0) of the spherical core and the surface hardness (Hs) of the spherical core is preferably 10 or less, more preferably 9.7 or less, and even more preferably 9.5 or less, in Shore C hardness. If the hardness difference (Hs-H0) is 10 or less, the spin performance during approach shots is good. The hardness difference (Hs-H0) is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more.
[0057] The spherical core has a center hardness (H0) of preferably 55 or more, more preferably 58 or more, and even more preferably 60 or more, in Shore C hardness, and preferably 77 or less, more preferably 75 or less, and even more preferably 73 or less.
[0058] The spherical core has a surface hardness (Hs) of preferably 60 or more, more preferably 63 or more, and even more preferably 65 or more, in Shore C hardness, and preferably 87 or less, more preferably 85 or less, and even more preferably 83 or less.
[0059] The diameter of the spherical core is preferably 34.8 mm or more, more preferably 36.8 mm or more, even more preferably 38.0 mm or more, and is preferably 42.2 mm or less, more preferably 41.8 mm or less, even more preferably 41.2 mm or less, and most preferably 40.8 mm or less.
[0060] When the diameter of the spherical core is 34.8 mm to 42.2 mm, the amount of compressive deformation (the amount of shrinkage of the spherical core in the compressive direction) from when an initial load of 98 N is applied to when a final load of 1275 N is applied is preferably 2.0 mm or more, more preferably 2.5 mm or more, even more preferably 3.0 mm or more, and is preferably 5.0 mm or less, more preferably 4.5 mm or less, even more preferably 4.0 mm or less. If the amount of compressive deformation is within the above range, the hitting feeling is better.
[0061] (Middle class) The golf ball of the present invention has an intermediate layer that encases the spherical core.
[0062] The intermediate layer composition constituting the intermediate layer preferably has a slab hardness (Hm) of 50 or more, more preferably 55 or more, and even more preferably 60 or more, in Shore D hardness. If the slab hardness (Hm) is 50 or more, in Shore D hardness, the distance performance during driver shots is good. Furthermore, the slab hardness (Hm) is preferably 74 or less, more preferably 72 or less, and even more preferably 70 or less, in Shore D hardness. When a golf club has a plurality of intermediate layers, the material hardness Hm is the material hardness of the intermediate layer composition constituting the outermost intermediate layer.
[0063] The thickness (Tm) of the intermediate layer is preferably 0.8 mm or more, more preferably 0.9 mm or more, and even more preferably 1.0 mm or more, and is preferably 3.0 mm or less, more preferably 2.6 mm or less, and even more preferably 2.2 mm or less. When there are multiple intermediate layers, the total thickness of all the intermediate layers is defined as the thickness Tm of the intermediate layers.
[0064] (Outermost cover) The golf ball of the present invention has an outermost cover layer located outside the intermediate layer.
[0065] The cover composition constituting the outermost cover layer preferably has a slab hardness (Hc) of 40 or less, more preferably 38 or less, and even more preferably 36 or less, in Shore D hardness. If the slab hardness (Hc) is 40 or less, in Shore D hardness, the shot feeling during approach shots is good. Furthermore, the slab hardness (Hc) is preferably 20 or more, more preferably 22 or more, and even more preferably 24 or more, in Shore D hardness. If the slab hardness (Hc) is 20 or more, the spin rate during driver shots is not too high, and the flight distance performance is good.
[0066] The intermediate layer composition forming the intermediate layer preferably has a slab hardness (Hm) greater than the slab hardness (Hc) of the cover composition forming the outermost cover layer. If the slab hardness (Hm) is greater than the slab hardness (Hc), the controllability of the flight distance on approach shots can be improved, and the spin rate on driver shots can be suppressed.
[0067] The hardness difference (Hm-Hc) between the slab hardness (Hm) and the slab hardness (Hc), in Shore D hardness, is preferably more than 0, more preferably 5 or more, more preferably 10 or more, and is preferably 50 or less, more preferably 48 or less, and even more preferably 46 or less.
[0068] The thickness (Tc) of the outermost cover layer is preferably 0.4 mm or more, more preferably 0.5 mm or more, and even more preferably 0.6 mm or more; and is preferably 1.0 mm or less, more preferably 0.9 mm or less, and even more preferably 0.8 mm or less.
[0069] (Cover composition, intermediate layer composition) The outermost cover layer and the intermediate layer are preferably formed from a resin composition containing a base resin.
[0070] Examples of base resins used in the resin compositions forming the outermost cover layer and the intermediate layer include ionomer resins, urethane resins (thermoplastic polyurethane elastomers, thermosetting polyurethane elastomers), thermoplastic styrene elastomers, thermoplastic polyamide elastomers, and thermoplastic polyester elastomers.
[0071] Examples of the ionomer resin include a binary ionomer resin in which at least a portion of the carboxyl groups in a binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms are neutralized with a metal ion; a ternary ionomer resin in which at least a portion of the carboxyl groups in a ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and an α,β-unsaturated carboxylic acid ester are neutralized with a metal ion; and a mixture thereof.
[0072] Examples of the binary ionomer resin include Himilan (registered trademark) 1555 (Na), 1557 (Zn), 1605 (Na), 1706 (Zn), 1707 (Na), AM7311 (Mg), AM7329 (Zn), and AM7337 (manufactured by Mitsui Dow Polychemicals); Surlyn (registered trademark) 8945 (Na), 9945 (Zn), 8140 (Na), 8150 (Na), 9120 (Zn), 9150 (Zn), 6910 (Mg), 6120 (Mg), 7930 (Li), 7940 (Li), and AD8546 (Li) (manufactured by DuPont); and Iotek (registered trademark) 8000 (Na), 8030 (Na), 7010 (Zn), and 7030 (Zn) (manufactured by ExxonMobil Chemicals).
[0073] Examples of the ternary ionomer resin include Himilan AM7327(Zn), 1855(Zn), 1856(Na), and AM7331(Na) (manufactured by Mitsui Dow Polychemicals); Surlyn 6320(Mg), 8120(Na), 8320(Na), 9320(Zn), 9320W(Zn), HPF1000(Mg), and HPF2000(Mg) (manufactured by DuPont); and Iotec 7510(Zn), 7520(Zn) (manufactured by ExxonMobil Chemicals). Note that Na, Zn, Li, Mg, and the like written in parentheses after the trade name of the ionomer resin indicate the metal species of these neutralizing metal ions.
[0074] The urethane resin has a urethane bond in its molecule. The urethane bond can be formed by a reaction between a polyol and a polyisocyanate. The polyol, which is a raw material for the urethane bond, has a plurality of hydroxyl groups, and a low molecular weight polyol and a high molecular weight polyol can be used.
[0075] Specific examples of the thermoplastic polyurethane elastomer include Elastollan (registered trademark) NY80A, NY84A, NY88A, NY95A, ET885, and ET890 (manufactured by BASF Japan Ltd.).
[0076] As the thermoplastic styrene-based elastomer, a thermoplastic elastomer containing a styrene block can be preferably used. The styrene block-containing thermoplastic elastomer has a polystyrene block as a hard segment and a soft segment.
[0077] The styrene block-containing thermoplastic elastomer includes styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), hydrogenated SBS, hydrogenated SIS, and hydrogenated SIBS. Hydrogenated SBS includes styrene-ethylene-butylene-styrene block copolymer (SEBS). Hydrogenated SIS includes styrene-ethylene-propylene-styrene block copolymer (SEPS). Hydrogenated SIBS includes styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS).
[0078] Examples of the thermoplastic styrene-based elastomer include TEFABLOC T3221C, T3339C, SJ4400N, SJ5400N, SJ6400N, SJ7400N, SJ8400N, SJ9400N, and SR04 (manufactured by Mitsubishi Chemical Corporation).
[0079] The resin composition (cover composition) forming the outermost cover layer preferably contains a urethane resin and / or an ionomer resin as a base resin, and more preferably contains a urethane resin. When the outermost cover layer contains a urethane resin as a base resin, the spin performance of the golf ball is further improved, and the spin amount in approach shots in particular is further improved.
[0080] When the cover composition contains a urethane resin as a base resin, the content of the urethane resin in the base resin is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The cover composition may contain only a urethane resin (preferably a thermoplastic urethane elastomer) as a base resin. When the cover composition contains an ionomer resin as a base resin, the content of the ionomer resin in the base resin is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination.
[0081] The resin composition forming the intermediate layer (intermediate layer composition) preferably contains an ionomer resin as a base resin. When the intermediate layer composition contains an ionomer resin, the resilience performance of the golf ball is improved, and the resilience performance in driver shots is particularly excellent. The content of the ionomer resin in the base resin of the intermediate layer composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination.
[0082] The resin composition forming the outermost cover layer and the intermediate layer may contain, in addition to the base resin described above, pigment components such as white pigments (e.g., titanium oxide), blue pigments, and red pigments, weight adjusters such as zinc oxide, calcium carbonate, and barium sulfate, dispersants, antioxidants, ultraviolet absorbers, light stabilizers, fluorescent materials, or fluorescent brighteners.
[0083] The content of the white pigment (e.g., titanium oxide) is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 6 parts by mass or less, based on 100 parts by mass of the base resin. By making the content of the white pigment 0.5 parts by mass or more, it is possible to impart hiding power to the intermediate layer and the outermost cover layer. In addition, if the content of the white pigment is 10 parts by mass or less, the durability of the obtained intermediate layer and the outermost cover layer is good.
[0084] The method for forming the intermediate layer is not particularly limited, but examples include a method in which the intermediate layer composition is first molded into a hemispherical half shell, two of which are used to encase a spherical core and then pressure molded, or a method in which the intermediate layer composition is directly injection molded onto the spherical core to encase the sphere.
[0085] Methods for molding the cover include, for example, a method in which a hollow shell is molded from the cover composition, and a sphere (a sphere with a spherical core or an intermediate layer) is coated with the multiple shells and compression molded (preferably, a method in which a hollow half shell is molded from the cover composition, and the sphere is coated with two half shells and compression molded), or a method in which the cover composition is directly injection molded onto the sphere.
[0086] The golf ball body with the molded cover is removed from the mold, and is preferably subjected to surface treatment such as deburring, cleaning, and sandblasting, as necessary.
[0087] If desired, a coating film or mark can be formed. The thickness of the coating film is not particularly limited, but is preferably 5 μm or more, more preferably 6 μm or more, even more preferably 7 μm or more, preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. If the thickness is 5 μm or more, the coating film is less likely to wear away even with continuous use, and if the thickness is 50 μm or less, the effect of the dimples can be fully obtained. Note that the coating film is very thin, so it does not impair the effect of the present invention.
[0088] (Golf ball structure) The golf ball of the present invention has a spherical core, an intermediate layer covering the spherical core, and an outermost cover covering the intermediate layer. The structure of the golf ball includes a three-piece golf ball consisting of an intermediate layer covering the spherical core and an outermost cover covering the intermediate layer, and a multi-piece golf ball (four-piece golf ball, five-piece golf ball, etc.) consisting of a single-layer spherical core, two or more intermediate layers covering the spherical core, and an outermost cover covering the intermediate layer.
[0089] The diameter of the golf ball of the present invention is preferably 40 mm to 45 mm. From the viewpoint of satisfying the standards of the United States Golf Association (USGA), the diameter is particularly preferably 42.67 mm or more. From the viewpoint of suppressing air resistance, the diameter is more preferably 44 mm or less, and particularly preferably 42.80 mm or less. In addition, the mass of the golf ball of the present invention is preferably 40 g to 50 g. From the viewpoint of obtaining large inertia, the mass is more preferably 44 g or more, and particularly preferably 45.00 g or more. From the viewpoint of satisfying the standards of the USGA, the mass is particularly preferably 45.93 g or less.
[0090] When the golf ball has a diameter of 40 mm to 45 mm, the amount of compressive deformation (amount of shrinkage in the compressive direction) when a final load of 1275 N is applied from an initial load of 98 N is preferably 2.0 mm or more, more preferably 2.1 mm or more, and even more preferably 2.2 mm or more, and is preferably 3.0 mm or less, more preferably 2.9 mm or less, and even more preferably 2.8 mm or less. If the amount of compressive deformation is within the above range, the shot feeling on a driver shot is good.
[0091] The surface hardness of the golf ball, in Shore D hardness, is preferably at least 45, more preferably at least 48, and even more preferably at least 50, and is preferably at most 65, more preferably at most 63, and even more preferably at most 61. If the surface hardness of the golf ball is within the above range, it will have excellent impact resistance and will be less susceptible to surface scratches.
[0092] An example of a golf ball of the present invention is shown in Figure 1. Figure 1 is a partially cutaway cross-sectional view showing a golf ball 2 according to one embodiment of the present invention. The golf ball 2 has a spherical core 4, an intermediate layer 6 that covers the spherical core 4, and an outermost cover layer 8 that covers the intermediate layer 6. A large number of dimples 10 are formed on the surface of the outermost cover layer 8. The portion of the surface of the golf ball other than the dimples 10 is a land 12. The golf ball 2 has a paint layer and a mark layer on the outside of the outermost cover layer 8, but these layers are not shown in the figure. EXAMPLES
[0093] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples, and all modifications and embodiments that do not deviate from the spirit of the present invention are included within the scope of the present invention.
[0094] [Evaluation method] (1) Compressive deformation amount (mm) A Yamada compression tester "SCH" was used to measure the amount of compressive deformation. In this tester, a golf ball or spherical core is placed on a metal hard plate. A metal cylinder is gradually lowered toward the golf ball or spherical core. The golf ball or spherical core is deformed when sandwiched between the bottom of the cylinder and the hard plate. The distance traveled by the cylinder from when an initial load of 98N is applied to the golf ball or spherical core until a final load of 1275N is applied is measured. The amount of compressive deformation (mm) is this distance traveled. The speed of travel of the cylinder until the initial load is applied is 0.83mm / s. The speed of travel of the cylinder from when the initial load is applied to when the final load is applied is 1.67mm / s.
[0095] (2) Core hardness (Shore C hardness) The hardness measured on the surface of the core was taken as the core surface hardness. The core was cut into a hemisphere, and the hardness was measured at the center of the cut surface and at a specified distance in the radial direction from the center. Each hardness was calculated by measuring the hardness at four points and averaging these values. The hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co., Ltd.). The detector used was "Shore C."
[0096] (3) Slab hardness (Shore D hardness) A sheet with a thickness of about 2 mm was prepared by injection molding using the resin composition and stored at 23° C. for two weeks. The hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co.) in a state where three or more sheets were stacked so as not to be affected by the measurement substrate, etc. The detector used was "Shore D."
[0097] (4) Golf ball surface hardness The hardness of the land portion of the surface of the golf ball was measured and taken as the ball surface hardness. Hardness was measured at four points and calculated by averaging these values. Hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co., Ltd.). The detector used was "Shore D".
[0098] (5) 7 iron test (I#7 shot) A No. 7 iron (Sumitomo Rubber Industries, Ltd., "XXIO (registered trademark) 12", shaft hardness: S, loft angle: 28°) was attached to a swing machine manufactured by Golf Laboratory. The impact point was set to the face center. The golf ball was hit under the condition of a head speed of 29 m / sec, and the ball speed, spin speed, peak height, and rolling distance (distance from the landing point to the stopping point) immediately after the hit were measured. The measurement was performed 12 times for each golf ball, and the average value was used as the measured value for that golf ball. The ball speed and spin speed were measured by taking continuous photographs of the golf ball immediately after it was hit. The peak height was measured using a trajectory measuring device (manufactured by TrackMan, "TRACKMAN (registered trademark) 4").
[0099] (6) Shot feeling Twenty golfers hit iron shots using a No. 7 iron (Sumitomo Rubber Industries, "XXIO (registered trademark) 12", shaft hardness: S, loft angle: 28°) and rated the feel of the ball on a three-point scale: hard, normal, or soft. Judgment criteria Excellent: 16 or more golfers rated the shot feel as soft Good: 12 or more golfers and 15 or less golfers rated the shot feeling as soft. Acceptable: 8 or more golfers and 11 or less golfers rated the shot feeling as soft. Poor: Seven or fewer golfers rated the shot feel as soft
[0100] [Manufacturing golf balls] (1) Preparation of spherical cores The raw materials were kneaded with a kneading roll so as to obtain the composition shown in Table 1, thereby obtaining a core composition. The core composition shown in Table 1 was hot-pressed in upper and lower molds having hemispherical cavities to obtain a spherical core. An appropriate amount of barium sulfate was added so that the mass of the resulting golf ball would be 45.3 g.
[0101] [Table 1]
[0102] The materials used in Table 1 are as follows: Polybutadiene rubber: JSR Corporation, "BR-730" (high cis polybutadiene rubber, cis-1,4-bond content 95% by mass, 1,2-vinyl bond content 1.3% by mass, Mooney viscosity (ML 1+4 (100℃))55, molecular weight distribution (Mw / Mn)3) Natural rubber: Dau Tieng Rubber Corporation, "CV60" (Mooney viscosity (ML 1+4 (100℃))=60) Methacrylic acid: Mitsubishi Gas Chemical Company, Inc. Zinc diacrylate: Nisshoku Techno Fine Chemical Co., Ltd., "ZN-DA90S" Zinc oxide: "Ginrei R" manufactured by Toho Zinc Co., Ltd. Barium sulfate: Sakai Chemical Industry Co., Ltd., "Barium Sulfate BD" Benzoic acid: Tokyo Chemical Industry Co., Ltd. (purity 98% or more) Bis(pentabromophenyl) disulfide: Kawaguchi Chemical Industry Co., Ltd. Diphenyl disulfide: Sumitomo Seika Chemicals Dicumyl peroxide: NOF Corporation, "Percumyl (registered trademark) D"
[0103] (2) Preparation of Resin Compositions (Composition for Intermediate Layer, Composition for Cover) The raw materials were extruded using a twin-screw kneading extruder so as to obtain the composition shown in Table 2, to prepare a pellet-shaped resin composition.
[0104] [Table 2] Surlyn® 8150: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by DuPont Himilan (registered trademark) 1605: Sodium ion-neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) AM7329: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1555: Sodium ion-neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1557: Manufactured by Mitsui Dow Polychemicals, zinc ion neutralized ethylene-methacrylic acid copolymer ionomer resin Tefablock T3221C: Thermoplastic styrene elastomer manufactured by Mitsubishi Chemical Corporation Elastollan (registered trademark) NY80A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY84A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY88A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY95A: BASF Japan, thermoplastic polyurethane elastomer Tinuvin (registered trademark) 770: BASF Japan, hindered amine light stabilizer Titanium dioxide: Ishihara Sangyo Kaisha, A-220
[0105] (3) Formation of the mid-layer and cover The resin composition (composition for intermediate layer) was injection molded onto a spherical core to obtain an intermediate layer-coated sphere. The obtained intermediate layer-coated sphere was placed into a final mold having a large number of pimples on the cavity surface. A half shell was obtained from the resin composition (composition for cover) by compression molding. Two half shells were coated onto the intermediate layer-coated sphere placed in the final mold to obtain a golf ball in which a large number of dimples were formed on the outermost cover in a shape that was the inverse of the pimples on the cavity surface. The evaluation results of the obtained golf ball are shown in Table 3.
[0106] [Table 3]
[0107] Golf balls No. 1 to 8 are formed from a rubber composition in which the spherical core contains natural rubber and methacrylic acid and / or its metal salt, and the hardness distribution of the spherical core satisfies the relationship of H0 < H 2.5 < H 5.0 < H 7.5 < H 10 < H 12.5 < H 15 < Hs. These golf balls No. 1 to 8 have a good hitting feeling during iron shots, a small rolling distance, and a low apex height. Therefore, these golf balls No. 1 to 8 have a good hitting feeling during iron shots, excellent controllability, and little influence of wind.
[0108] Golf balls No. 9 to 13 are the case where the spherical core is formed from a rubber composition that does not contain natural rubber and methacrylic acid and / or its metal salt. These golf balls No. 9 to 13 have a high apex height and a large rolling distance during iron shots. Therefore, these golf balls No. 9 to 13 are greatly affected by wind and have poor controllability during iron shots.
[0109] (Aspect of the present invention) The present invention (1) has a spherical core, an intermediate layer covering the spherical core, and an outermost layer cover covering the intermediate layer. The spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator. The base rubber contains natural rubber, the co-crosslinking agent contains methacrylic acid and / or its metal salt, and the center hardness (H0) of the spherical core, the hardness (H 2.5 ) at a point 2.5 mm in the radial direction from the center of the spherical core, the hardness (H 5.0 ) at a point 5.0 mm in the radial direction from the center of the spherical core, the hardness (H 7.5 ) at a point 7.5 mm in the radial direction from the center of the spherical core, the hardness (H 10 ) at a point 10 mm in the radial direction from the center of the spherical core, the hardness (H 12.5) The hardness (H) at a point 15 mm radially from the center of the spherical core 15 ) and the surface hardness (Hs) satisfy the relationship H0 < H 2.5 < H 5.0 < H 7.5 < H 10 < H 12.5 < H 15 < Hs, and is a golf ball characterized by satisfying this relationship.
[0110] In the present invention (2), the core hardness (H0), hardness (H 2.5 ), hardness (H 5.0 ), hardness (H 7.5 ), hardness (H 10 ), hardness (H 12.5 ), hardness (H 15 ), and surface hardness (Hs) are measured in Shore C hardness, and H 2.5 - H0 < 4, H 5.0 - H 2.5 < 4, H 7.5 - H 5.0 < 4, H 10 - H 7.5 < 4, H 12.5 - H 10 < 4, H 15 - H 12.5 < 4, and Hs - H 15 < 4, and is the golf ball according to the present invention (1).
[0111] In the present invention (3), the hardness difference (Hs - H0) between the core hardness (H0) of the spherical core and the surface hardness (Hs) of the spherical core is 10 or less in Shore C hardness, and is the golf ball according to the present invention (1) or (2).
[0112] In the present invention (4), the content of the natural rubber is 10% to 90% by mass in 100% by mass of the base rubber, and is the golf ball according to any one of the present inventions (1) to (3).
[0113] In the present invention (5), the slab hardness of the intermediate layer composition forming the intermediate layer is greater than the slab hardness of the cover composition forming the outermost layer cover, and is the golf ball according to any one of the present inventions (1) to (4).
[0114] The present invention (6) is the golf ball according to any one of the present inventions (1) to (5), wherein the cover composition forming the outermost cover layer is a resin composition containing a urethane resin as a base resin, and the cover composition forming the outermost cover layer has a slab hardness, in Shore D hardness, of 40 or less.
[0115] The present invention (7) is a golf ball according to any one of the present inventions (1) to (6), wherein the intermediate layer composition forming the intermediate layer is a resin composition containing an ionomer resin as a base resin, and the intermediate layer composition forming the intermediate layer has a slab hardness of 50 or more in Shore D hardness. [Explanation of symbols]
[0116] 2: Golf ball, 4: Spherical core, 6: Intermediate layer, 8: Outermost cover, 10: Dimples, 12: Land
Claims
1. A golf ball has a spherical core, a mid layer encasing the spherical core, and an outermost cover encasing the mid layer, the spherical core is formed from a rubber composition containing a base rubber, a co-crosslinking agent, and a crosslinking initiator, The base rubber contains natural rubber, The co-crosslinking agent contains methacrylic acid and / or a metal salt thereof, The central hardness (H0) of the spherical core, and the hardness (H 2.5 ), hardness at a radial distance of 5.0 mm from the center of the spherical core (H 5.0 ), hardness at a radial distance of 7.5 mm from the center of the spherical core (H 7.5 ), hardness at a radial distance of 10 mm from the center of the spherical core (H 10 ), hardness at a radial distance of 12.5 mm from the center of the spherical core (H 12.5 ), hardness at a radial distance of 15 mm from the center of the spherical core (H 15 ) and surface hardness (Hs), H0<H 2.5 <H 5.0 <H 7.5 <H 10 <H 12.5 <H 15 <Hs.
2. The center hardness (H0), hardness (H 2.5 ), hardness (H 5.0 ), hardness (H 7.5 ), hardness (H 10 ), hardness (H 12.5 ), hardness (H 15 ) and surface hardness (Hs) in Shore C hardness: H 2.5 -H0<4、 H 5.0 -H 2.5 <4、 H 7.5 -H 5.0 <4、 H 10 -H 7.5 <4、 H 12.5 -H 10 <4、 H 15 -H 12.5 <4, and Hs-H 15 2. The golf ball according to claim 1, which satisfies the relationship: <EMI ID=13.1><4.
3. 2. The golf ball according to claim 1, wherein the difference in hardness (Hs-H0) between the center hardness (H0) of the spherical core and the surface hardness (Hs) of the spherical core is 10 or less in Shore C hardness.
4. 2. The golf ball according to claim 1, wherein the content of the natural rubber is 10% by weight to 90% by weight based on 100% by weight of the base rubber.
5. 2. The golf ball according to claim 1, wherein the slab hardness of the intermediate layer composition forming the intermediate layer is greater than the slab hardness of the cover composition forming the outermost cover layer.
6. the cover composition forming the outermost cover layer is a resin composition containing a urethane resin as a base resin, 2. The golf ball according to claim 1, wherein the cover composition forming the outermost cover layer has a slab hardness of 40 or less in Shore D hardness.
7. the intermediate layer composition forming the intermediate layer is a resin composition containing an ionomer resin as a base resin, 2. The golf ball according to claim 1, wherein the intermediate layer composition forming the intermediate layer has a slab hardness of 50 or more in Shore D hardness.
Citation Information
Patent Citations
Golf ball for exercise field
JP1985092780A
Golf ball for exercise field
JP1986071069A